Socket preservation - Nurhaeini, Caecilia Susetya Wahyu; Komara, Ira (Padjadjaran Journal of Dentistry, 2015)
Alveolar ridge will commonly decrease in volume and change morphologically, as a result of a tooth loss. These changes are usually clinically significant and can make placement of a conventional protesaÂ  or an implant more difficult. Socket preservation after tooth extraction can minimize ridge resorption. By using socket preservation techniques, it is possible to preserve the height and width of the ridge. Socket preservation can be done by atraumatic tooth extraction, placement of bone graft material, membrane, combination of bone graft and membrane, and connective tissue graf.